Distribution of HbS Allele and Haplotypes in a Multi-Ethnic Population of Guinea Bissau, West Africa: Implications for Public Health Screening - Martella, Maddalena; Campeggio, Mimma; Pulè, Gift; Wonkam, Ambroise; Menzato, Federica; Munaretto, Vania; Viola, Giampietro; Da Costa, Sabado P.; Reggiani, Giulia; Araujo, Antonia; Cumbà, Dionisio; Liotta, Giuseppe; et al. (Frontiers in Pediatrics, 2022)
Background: Sickle Cell Disease (SCD) is an inherited condition that is widespread globally and especially in malaria-endemic West African countries. Limited epidemiological data on SCD are available for Guinea Bissau, where newborn screening is not yet implemented, routine diagnosis is not available and care is case directed. Methods: Dried blood spots were collected from children accessing two hospitals managed by Italian Non-Governmental Organizations in the capital city of Bissau and sent to Padova for Hemoglobin (Hb) quantification through HPLC and molecular analysis. Beta globin gene analysis was performed in all; Hb haplotype of the HbSS and HbSA patients was performed in South Africa. 100 samples belonging to the most frequent ethnic groups were randomly selected for detection of G6PD mutations. Results: Samples from 848 consecutive children (498 M and 350 F, mean age 6.8 years) accessing the two hospitals were analysed: 6.95% AS (4.42% allelic frequency), 0.94% SS, and 0.23% AC. 376G G6PD allelic frequency was 24%; 14.8% in AS individuals. The Senegal haplotype was the most prevalent (31%), and the proposition of chromosomes with the atypical haplotype was surprisingly high (56%). Conclusion: Our study demonstrates a significant frequency of the HbS allele in the population of Guinea Bissau supporting the implementation of screening strategies. The differences among ethnic groups can help guide targeted interventions for SCD awareness campaigns and determine priority areas for public health interventions. The pilot analysis on haplotypes reveals a large proportion of the atypical haplotype which may be indicative of a genetically heterogeneous population.